2019
DOI: 10.1021/acsnano.8b09732
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and Density Dynamics of Excitons in a Single-Layer MoS2 Reaching the Homogeneous Limit

Abstract: We measure the coherent nonlinear response of excitons in a single layer of molybdenum disulfide embedded in hexagonal boron nitride, forming a h-BN/MoS2/h-BN heterostructure. Using four-wave mixing microscopy and imaging, we correlate the exciton inhomogeneous broadening with the homogeneous one and population lifetime. We find that the exciton dynamics is governed by microscopic disorder on top of the ideal crystal properties. Analyzing the exciton ultrafast density dynamics using amplitude and phase of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 57 publications
3
39
0
Order By: Relevance
“…Our space-, time-, and excitation/detection-frequency-resolved spectroscopy provides a unique tool to measure EXPC also in other TMDs. hBN encapsulation can lower inhomogeneous broadening of 1L-TMDs 67 , 68 , we thus expect better resolved peaks for hBN-encapsulated samples. S may be influenced by the substrate, by changing the macroscopic electric field induced by the polar LO phonon at the interface 60 .…”
Section: Resultsmentioning
confidence: 92%
“…Our space-, time-, and excitation/detection-frequency-resolved spectroscopy provides a unique tool to measure EXPC also in other TMDs. hBN encapsulation can lower inhomogeneous broadening of 1L-TMDs 67 , 68 , we thus expect better resolved peaks for hBN-encapsulated samples. S may be influenced by the substrate, by changing the macroscopic electric field induced by the polar LO phonon at the interface 60 .…”
Section: Resultsmentioning
confidence: 92%
“…By using FWM imaging, it is found that the nonlinear excited absorption of excitons and their coherent coupling can be observed at such a position ( Figure 14 a) [ 103 ]. Similar methods are also used in related research [ 105 , 106 , 107 ].…”
Section: Characterization Of 2d Materials Propertiesmentioning
confidence: 99%
“…[1][2][3][4] Such methods of ultrafast coherent spectroscopy are also employed in fundamental studies of excitons (EX), bound complexes of electrons and holes, hosted by emerging material systems and their nanostructures, such as colloidal quantum dots , 5 nanoplatelets , 6 perovskites , 7 single-layers (SLs) of semiconducting transition metal dichalcogenides 8 (TMDs) and their van der Waals heterostructures . 9 energy of several hundreds meV. With such a high binding energy -stemming from the two-dimensional confinement, reduced dielectric screening and high carrier effective masses -light-matter interaction is expected to be enhanced with respect to conventional semiconductors, like GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an example of EX population dynamics measured via FWM was reported and discussed in Ref. [9] using MoS 2 heterostructure.…”
Section: Introductionmentioning
confidence: 99%